Meaning and normativity - Gibbard, Allan (Oxford : Oxford University Press, 2012)
The concepts of meaning and mental content resist naturalistic analysis. This is because they are normative: they depend on ideas of how things ought to be. This text offers an explanation of these 'oughts', borrowing devices from metaethics to illuminate deep problems at the heart of the philosophy of language and thought.
Description based on online resource; title from home page (viewed on Jan. 4, 2013).
Includes bibliographical references and index.
Keywords: Meaning (Philosophy); Normativity (Ethics)